3D Data for Better Property Value Estimation in the context of LADM Valuation Information Model - Kara, A. (2020)
The purpose of this paper is to examine which geospatial analyses, especially 3D analyses, can be used to provide information about immovable properties including environmental and locational characteristics for property valuation activities. Furthermore, it is investigated that how property valuation can benefit from data sources including semantically rich 3D building, city and cadastral models for deriving environmental and locational characteristics of property units. To achieve these objectives, the data sources and geospatial analyses are initially investigated in the context of property valuation. Then, the paper focuses more on viewshed analysis. By using open topography, building and height datasets of the Netherlands and 3D GIS analysis, a viewshed analysis is presented to show how it can be utilized using different data sources for better nderstanding and explanation of values of the properties. The paper is concluded with a discussion to what extent it is possible and meaningful to include (derived) environmental characteristics of properties in the LADM Valuation Information Model.